THE JUDICIAL PROTECTION AGAINST COPYRIGHT HOLDERS FROM MUSIC PIRACY IN DIGITAL ERA - Saifudin, Mokhamad; Rosmaya, Ina (jfpublisher, 2022)
Copyright is the exclusive right of creator which is created based on declarative principles and is realized in material form without prejudice to the limitations of legalation provisions. There are several artworks, one of them is music. The objective of this research is to find out the implementation of judicial protection for copyright holders in Indonesia and to analyze the judicial protection against copyright holders from music piracy in digital era. The method used in this research is descriptive qualitative method and the research type is normative. There are two problem statements of this research, these are (1) how implementation of judicial protection for copyright holders in Indonesia; (2) how implementation of judicial protection against copyright holders from music piracy in digital era. Meanwhile, the approach used in this research is case approach which an approach used applicable regulatory parameters to solve law issues, and the issue in this research is legal protection against copyright holders from music piracy in digital era. This research analysis used library research. Nowadays, the piracy issue especially in music piracy is widespread in Indonesia. Therefore, the government must to protect all copyrighted works of creators from pirating artworks such as supervise and control the development of illegal websites in digital era.